Analisis Perilaku Konsumen Dan Brand Equity Terhadap Keputusan Menabung Di Bank Muamalat Indonesia Cabang XXXXX - Fatkhuri Wahmad; Rohmat Rospari (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2019)
Bank Muamalat as one of the national private banks faces the same challenges as other banks. Namely increasingly fierce competition between banks in attracting third party funds (TPF) from customers or customers. One way to collect third party funds is through savings. To attract banking customers must know the characteristics and desires of the community. That way the products offered can be accepted by prospective customers. Banks must identify how consumers decide to choose savings products. Then formulate the right marketing strategy. This study aims to determine how much influence the behaviour of consumers on savings decisions. Second, knowing the effect of brand equity on saving decisions. And find out the influence of consumer behaviour and brand equity together on saving decisions. The study was conducted on customers at Bank Muamalat Indonesia, XXXXX Branch through a descriptive analytic survey using a Likert scale model. The results showed that there was an influence of consumer behaviour on the decision to save. Likewise, it can be concluded that promotion or band equity by banking marketing has the most significant influence on consumers' decision to save.